2020
DOI: 10.1152/ajplung.00007.2019
|View full text |Cite
|
Sign up to set email alerts
|

Episodic stimulation of central chemoreceptor neurons elicits disordered breathing and autonomic dysfunction in volume overload heart failure

Abstract: Enhanced central chemoreflex (CC) gain is observed in volume overload heart failure (HF) and is correlated with autonomic dysfunction and breathing disorders. The aim of this study was to determine the role of the CC in the development of respiratory and autonomic dysfunction in HF. Volume overload was surgically created to induce HF in male Sprague-Dawley rats. Radiotelemetry transmitters were implanted for continuous monitoring of blood pressure and heart rate. After recovering from surgery, conscious unrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…Non-ischemic chronic heart failure (CHF) was produced by the surgical creation of an arteriovenous shunt between the abdominal aorta and the cava vein to induced chronic volume overload [ 16 , 17 , 31 34 ]. Under anesthesia (induction with 5% of isoflurane and 2% for maintenance, balance with O 2 ) laparotomy was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-ischemic chronic heart failure (CHF) was produced by the surgical creation of an arteriovenous shunt between the abdominal aorta and the cava vein to induced chronic volume overload [ 16 , 17 , 31 34 ]. Under anesthesia (induction with 5% of isoflurane and 2% for maintenance, balance with O 2 ) laparotomy was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Recordings were made from the left parasternal short-axis view. An increase of 1.5-fold in the end diastolic volume (EDV) and stroke volume (SV) relative to sham condition were the criteria for CHF [ 16 , 17 , 31 , 33 , 34 ]. Left ventricle (LV) end diastolic and systolic diameter (LVEDD and LVESD, respectively) were measured from 3 consecutive cycles.…”
Section: Methodsmentioning
confidence: 99%
“…However, disordered breathing and autonomic dysfunction are pathophysiological hallmarks of heart failure. Using a heart failure rat model where chemoreceptors of the retrotrapezoid nucleus (RTN) were destroyed, DÍAZ et al [35] showed that episodic hypercapnia stimulation triggers ventilator plasticity and elicits cardiorespiratory abnormalities that depend on RTN neurons. Using the same model but eliminating the brainstem pre-sympathetic neurons (RVLM-C1) instead, DEL RIO et al [36] showed that they play a major role in development/maintenance of irregular breathing pattern.…”
Section: Insights Into the Pathophysiology Of Sdbmentioning
confidence: 99%
“…Using a heart failure rat model where chemoreceptors of the retrotrapezoid nucleus (RTN) were destroyed, D íaz et al . [ 35 ] showed that episodic hypercapnia stimulation triggers ventilator plasticity and elicits cardiorespiratory abnormalities that depend on RTN neurons. Using the same model but eliminating the brainstem pre-sympathetic neurons (RVLM-C1) instead, D el R io et al .…”
Section: Insights Into the Pathophysiology Of Sdbmentioning
confidence: 99%
“…These articles center on a variety of topics such as sex differences and estrogen signaling in RV function in PH (9,18); effects of perinatal hyperoxia or hypoxia on RV function later in life (10,15); effects of HIV, opioids, or vaping on endothelial function and cardiorespiratory parameters (1, 3); bone morphogenetic protein receptor 2 (BMPR2) regulation of insulin and glucose signaling in cardiomyocytes ( 13); interdependence of RV glucose uptake, hypoxia and ␤-adrenergic receptor signaling in PH (28); effects of pulmonary vascular thrombospondin 1/CD47 signaling on RV afterload in sickle cell disease (22); differences in mesothelial mobilization between the developing lung and heart (19); and effects of episodic hypercapnic stimulation on respiratory-cardiovascular coupling in volume-overload heart failure (6). Two studies assessed the effects of established treatments for pulmonary arterial hypertension (PAH; used in combination with other established or emerging PAH treatments) on RV adaptation, using novel end points or novel delivery methods (16,23).…”
mentioning
confidence: 99%